Risk of Pregnancy in Breastfeeding Mothers: Role of the Progesterone Vaginal Ring on Birth Spacing - Regine Sitruk-Ware; Saumya Ramarao; Ruth Merkatz; John Townsend (European Medical Journal, 2016)
The progesterone vaginal ring (PVR) Progering® has been shown to be effective as a contraceptive in breastfeeding women who need safe and effective methods of spacing pregnancies. Previous clinical trials, of 1-year duration, demonstrated its efficacy to be similar to that of the intra-uterine device (IUD) during lactation. The duration of lactational amenorrhoea is significantly prolonged in PVR users in comparison with IUD users with fewer median numbers of bleeding/spotting episodes and days. This delivery system designed for 3-month use needs to be renewed every 3 months as long as breastfeeding continues, for up to 1 year. The frequency of breastfeeding, breast milk volume, and infant growth were not different in PVR or IUD users, and the safety of this new method has been well documented. This article reviews the literature and describes the mechanism of action of the PVR during lactation to bring additional protection over exclusive breastfeeding only, during the first year postpartum. Further evaluation of the PVR acceptability in different populations where breastfeeding is popular and highly recommended for the infant's benefit is warranted.